2023
DOI: 10.1021/acsami.3c02762
|View full text |Cite
|
Sign up to set email alerts
|

Cleavable-Branched Polymer-Modified Liposomes Reduce Accelerated Blood Clearance and Enhance Photothermal Therapy

Abstract: In recent years, cationic liposomes have been successfully used as delivery platforms for mRNA vaccines. Poly­(ethylene glycol) (PEG)-lipid derivatives are widely used to enhance the stability and reduce the toxicity of cationic liposomes. However, these derivatives are often immunogenic, triggering the rise of anti-PEG antibodies. Understanding the role and impact of PEG-lipid derivatives on PEGylated cationic liposomes is key to solving the PEG dilemma. In this study, we designed linear, branched, and cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…It has been found that tumor cells are rich in vascular structure, and their endothelial interstitial space is sparse and incomplete; thus, macromolecules and lipids are able to selectively pass through and stay in the tumor cells. Therefore, if the selectivity of AIE materials is improved through the use of nanocarrier technology, so that the AIE materials are more aggregated in the tumor cells and the drug concentration in the tumor is increased, the enhanced antitumor therapy can be better achieved. Liposome is a spherical bilayer vesicle structure, whose phospholipid bilayer has an outer surface layer formed by a hydrophilic head and a hydrophobic tail in the middle part of the membrane; due to this special structure, the liposome is therefore capable of carrying not only hydrophilic substances but also hydrophobic substances. In practical applications, a variety of smart-responsive nanocarriers can be prepared by combining stimulus-responsive factors (e.g., pH, temperature, enzymes, etc.) with liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that tumor cells are rich in vascular structure, and their endothelial interstitial space is sparse and incomplete; thus, macromolecules and lipids are able to selectively pass through and stay in the tumor cells. Therefore, if the selectivity of AIE materials is improved through the use of nanocarrier technology, so that the AIE materials are more aggregated in the tumor cells and the drug concentration in the tumor is increased, the enhanced antitumor therapy can be better achieved. Liposome is a spherical bilayer vesicle structure, whose phospholipid bilayer has an outer surface layer formed by a hydrophilic head and a hydrophobic tail in the middle part of the membrane; due to this special structure, the liposome is therefore capable of carrying not only hydrophilic substances but also hydrophobic substances. In practical applications, a variety of smart-responsive nanocarriers can be prepared by combining stimulus-responsive factors (e.g., pH, temperature, enzymes, etc.) with liposomes.…”
Section: Introductionmentioning
confidence: 99%